Las obligaciones tributarias en la Empresa Dimaxy de la ciudad de Quito del año 2014 y su incidencia en la planificación Tributaria para el año 2015. - Maza Caz, Ana Cecilia (2016)
In this research, it was analyzed the influence of alcoholism in the working memory of the members of This research was carried on a private sector company, exactly the wholesale distributor "DIMAXY" the company is engaged in the distribution and marketing of consumer products wholesale and retail, in the city of Quito, Province Pichincha. The concern to meet tax obligations to the Internal Revenue Service has determined the need to propose adequate Tax Planning, as an appropriate means to achieve the objective of "DIMAXY" having no legal problem with Tax administration. Chapter I is exposed and describes the problem that is under investigation, justification to put it as such and the objectives expected to meet once solved it. Chapter II are the research background of the subject, theoretical foundation it enabled clear the two variables under study, operacionabilidad, Chapter III inductive methodology was applied, deductive, descriptive, documentary, field, exploratory and descriptive, a survey was conducted to managers and staff of the accounting department where the information was tabulated and plotted with their analysis and interpretation, then the conclusions and recommendations were developed, is also a comparative analysis of the tax obligations of the company Dimaxy was developed the fiscal period 2014. Finely it concludes with a proposal, the same that will improve compliance with the obligations of that entity.